(Des)construindo identidades: narrativas de professoras negras de língua inglesa - Layenne Humberto de Oliveira (2020)
The present study investigated racial and professional identities of black female English teachers, emphazising black identity and language teacher identity. Its purpose was to understand possible conncetions between the two social identities by using narratives aimed at exploring the processes involved in the construction of those identities. The qualitative methodology involved a case study and the narratives were built based on semi-structured interviews, questionnaires and surveys. Results indicated that the teachers build their professional and racial identities in a complex and dynamic process throughout their tecahing careers and personal experiences as black women. Results also show that racial and professional identities are deeply intertwined, since teacher identity is constantly affected by the perspective of English as racialized language. The relation between whitness and English language teaching influences induces students to question the legitimacy of the women’s position as teachers, interfering in their classroom practice and in the way their identities are negotiated.